IMPLEMENTASI KERAHASIAAN INFORMASI MEDIS DALAM REKAM MEDIS PASIEN ( Studi Kasus di Rumah Sakit Islam AT-TIN HUSADA Ngawi Jawa Timur) - Rahardjo, Budhi (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2019)
The implementation of the confidentiality of medical record documents at RSI AT-Tin Husada Ngawi which is still not kept confidential, it can be seen from the patient's medical record documents in the insurance department and in the BPJS unit more than 24 hours for claims purposes, the medical records of inpatients should be 2x 24 hours must be returned to the medical record unit.This type of research is descriptive qualitative. The study was conducted at RSI AT-Tin Husada Ngawi in September 2018. The subjects were medical records officers, doctors and patients, using the Observation and Interview method, using a retrospective and the technique used was purposive sampling. The population here is the medical records of patients and doctors, data analysis with flow models.The results of research at RSI AT-Tin Husada Ngawi, there are 3 ownership of medical record documents in the Hospital, namely: Belonging to the hospital, public property or third party property, owned by the patient. The information the doctor gives the patient about the patient's illness is clear and before medical treatment the patient must complete the informed consent form. But to protect the rights of patients to the confidentiality of the contents of medical records at RSI AT-Tin Husada Ngawi, it is not yet in accordance with the Minister of Health Regulation No.269/Menkes/Per/III/2008.It is recommended that RSI AT-Tin Husada Ngawi need a clear and clear SOP about the return of medical record files.